Short-term effects of midseason coach turnover on team performance in soccer - Balduck, A.-L.; Buelens, M.; Philippaerts, R. (Research Quarterly for Exercise and Sport, 2010)
The present study addressed the issue of short-term performance effects of midseason coach turnover in soccer. Although there are several reasons for changing coaches, midseason change is often associated with poor team performance (Rowe, Cannella, Rankin, & Gorman, 2005) and considered to be a way to reap short-term dividends in performance improvement (Audas, Dobson, & Goddard, 2002; Salomo & Teichmann, 2000). Koning (2003) and McTeer and White (1995) argued that the focus on midseason coach turnover is relevant in soccer, as the team composition usually changes significantly between seasons.